The non‐directed living kidney donor: Why donate to strangers?. Issue 2 (13th March 2019) - Balliet, Wendy; Kazley, Abby S.; Johnson, Emily; Holland‐Carter, Lauren; Maurer, Stacey; Correll, Jennifer; Marlow, Nicole; Chavin, Kenneth; Baliga, Prabhakar
SUMMARY: Background: Kidney transplantation improves survival and quality of life for patients with end‐stage kidney disease (ESKD). However, there is a shortage of donated organs, resulting in long wait times and the potential for death before a donor is found. Non‐directed (also called altruistic) living kidney donation is a growing type of donation; however, few studies have examined the values and motivation of individuals evaluated to be a non‐directed donor. Objectives: This qualitative study explores the motivations and values of individuals evaluated for non‐directed donation. Design: Focus groups were conducted with individuals who had been evaluated for non‐directed living kidney donation. Grounded theory method guided the data analysis. Participants: Participants (N = 11) were individuals who completed the evaluation for a non‐directed living kidney donation. Findings: Qualitative analyses revealed eight major themes participants considered in making their decision to donate to a non‐related person: (i) motivation to donate; (ii) minimise perceived risk; (iii) ideal selected recipient; (iv) change in lifestyle; (v) source of donation knowledge; (vi) history of altruistic acts; (vii) donation chain and (viii) others' response. Conclusions: Results suggest that non‐directed living kidney donors think deeply about their decision and have a resolve to help others that is aligned with their values. As organ availability remains at a critical shortage, unwillingness to consider non‐directed living donors (NDD) due to beliefs of ill motivations appears unsupported. Future directions call for the need of standard practice of care in kidney donation evaluations across transplant centers.